2012
DOI: 10.1016/j.bbrc.2012.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized phospholipids impair pulmonary antibacterial defenses: Evidence in mice exposed to cigarette smoke

Abstract: Patients with COPD are associated with poor pulmonary anti-bacterial innate defenses, which increase the risk for frequent acute exacerbations caused by bacterial infection. Despite elevated numbers of phagocytes (macrophages and neutrophils), airways of patients with COPD show stable bacterial colonization. A defect in the phagocytic ability of alveolar macrophages (AMs) is one of the primary reasons for failure to clear the invading bacteria in airways of smokers and COPD patients and also in mice exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 31 publications
(53 reference statements)
1
48
0
Order By: Relevance
“…PPARγ is known to activate lipid metabolism [10]. It has recently been shown that cigarette smoke exposure leads to the generation of modified phospholipids that inhibit phagocytosis of bacteria [22]. Therefore, PPARγ activation may help in processing inhibitory phospholipids from the extracellular lung environment to allow binding of the bacteria by alveolar macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARγ is known to activate lipid metabolism [10]. It has recently been shown that cigarette smoke exposure leads to the generation of modified phospholipids that inhibit phagocytosis of bacteria [22]. Therefore, PPARγ activation may help in processing inhibitory phospholipids from the extracellular lung environment to allow binding of the bacteria by alveolar macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ activation does not restore phagocytic activity of alveolar macrophages Cigarette smoke exposure has been shown to compromise phagocytic activity of alveolar macrophages [21,22]. We next investigated if rosiglitazone treatment restored the phagocytic activity of alveolar macrophages ex vivo.…”
Section: Pparγ Activation Reduces Bacterial Exacerbation Of Cigarettementioning
confidence: 99%
“…78 Indeed, T15/E06 IgM has been found to prevent OxPAPC (oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine)–induced IL-6 secretion by macrophages 79 and to block the ability of OxPL to decrease macrophage phagocytosis. 80 Many more natural IgMs with specificity for other OSEs exist, which represent a prominent fraction (20%–30%) of all natural IgMs in mice and humans. 66 For example, IgM with specificity for malondialdehyde epitopes, such as the natural IgM NA17, also bind apoptotic cells and enhance the in vivo clearance of injected apoptotic cells by peritoneal macrophages.…”
Section: Igm: the House Keepermentioning
confidence: 99%
“…Furthermore, NF-kB is upregulated leading to an increased expression of proinflammatory cytokines and an increased activation of recruited immune cells. Furthermore, high levels of ROS can induce the formation of oxygenated phospholipids, which potently inhibit phagocytic activity of alveolar macrophages [62,106]. The dysfunction of these cells is thought to be the reason COPD patients show stable bacterial colonization, despite the increased infiltration of phagocytic cells in the lungs.…”
Section: Oxidative Stressmentioning
confidence: 99%